Study of pulsed-DC sputtering induced Ge2Sb2Te5 thin films using facile thermoelectric measurement. (15th May 2016) - Kumar, Manish; Vora-ud, Athorn; Seetawan, Tosawat; Han, Jeon Geon
Abstract: Thermoelectric measurement is an exhaustive exercise for the case of thin films, requiring meticulous attention to the thermal contact interfaces and the instrumentation. Usually, different set-ups are combined for the temperature dependent measurement of different thermoelectric key quantities. Here, a facile 6-probe measurement set-up is presented, which can measure Seebeck coefficients and electrical properties of thin films in the temperature range of 300 K–600 K. Using this set-up, the thermoelectric properties of Ge2 Sb2 Te5 thin films, prepared with pulsed DC magnetron sputtering method are studied. The effects of working pressure, post-deposition thermal treatment and variation of film thickness on the microstructure, surface, electrical and thermoelectric properties are investigated systematically. Plasma diagnostics, performed using optical emission spectroscopy provided the information about various radicals' excitations and the electron temperature. Microstructural studies show the phase transformation from amorphous to metastable cubic phase. FESEM study exhibits highly dense films with uniform grains compactness. It has been found that lowering average crystallite size by optimum electron temperature and pressure conditions governs the enhancement in Seebeck coefficient. The throughput of process > 400 nm/min, and obtained Seebeck coefficients values 271.50 μV/K are highly promising for industrial utilization. Graphical abstract: Highlights: Developed a facile thin films thermoelectric measurement system to be used in the temperature range of 300 K–600 K. Presented the plasma diagnostics during pulsed DC magnetron sputtering plasma process for Ge2 Sb2 Te5 thin films. Lowering of average crystallite size in metastable cubic phase enhances the Seebeck coefficient. Obtained throughput of process > 400 nm/min, and Seebeck coefficients 271.50 μV/K, highly promising for industrial utilization.